메타분석을 통한 영어 교과에서의 문법 교육의 효과 분석 - 이제영(Je-Young Lee) (한국콘텐츠학회 논문지, 16(1), 2016)
This study aims to investigate the overall effects of teaching grammar in the Korean EFL classroom. A meta-analysis of 67 research findings in 30 articles was conducted to synthesize the results of these studies by calculating the mean effect sizes. This study reviewed and analyzed the previous studies in terms of subjects, treatment period, and types of grammar teaching. The results showed that teaching grammar in the classroom had beneficial effects on learners in general (d=.907). It was found to be more effective for middle school and university students than for elementary and high school students (Q=37.065, df=3, p=.000). There was no statistically significant difference in terms of treatment period and types of grammar teaching. Pedagogical implications and suggestions for Korean EFL learners are also discussed. 본 연구는 EFL 상황인 한국 영어 교실 수업에서의 문법 교육의 효과를 통합적으로 살펴보는 목적을 갖고 있다. 이를 위해 총 30개 논문에 수록된 67개의 개별 연구 결과를 토대로 메타분석을 실시하였고, 이를 통해 평균효과크기를 산출하였다. 또한 조절변인별 문법 교육의 효과를 비교해 보기 위해 각 연구를 연구대상, 처치 기간, 문법 교육의 종류를 기준으로 분류하여 분석하였다. 그 결과 문법 교육 연구 전체의 평균 효과크기는 .907로 매우 높은 효과를 지니고 있는 것으로 나타났다. 또한 연구대상별 비교에서 중학생과 대학생 대상의 문법교육 효과가 초등학생과 고등학생 대상으로 한 경우보다 통계적으로 유의한 수준에서 높은 효과를 지니고 있는 것으로 나타났다 (Q=37.065, df=3, p=.000). 반면 처치기간과 문법 교육의 유형을 기준으로 비교해 봤을 때는 효과의 차이는 나타나지 않았다.